(untitled) (EDUCATION IN THE 21ST CENTURY, 2025)
The event-based approach is considered by the authors of the article as an effective methodological basis for designing a personalized educational environment for primary school students with disabilities. Taking into account the need to ensure equal access to educational resources for all participants in educational relations, as well as the demand for an effective personalized educational environment for children with disabilities, taking into account the specific characteristics and needs of students, as well as the dynamics of their development, the event-based approach appears justified from a scientific and pedagogical point of view, the theory of providing special conditions for the development of each child’s individual identity in purposefully created specific circumstances of "living" the experience of an emotional and valuable attitude to joint activities. The criteria for determining the effectiveness of the educational environment for primary school students with disabilities, according to the paradigm of the event approach, are: flexibility of the educational environment (indicators: barrier-free functional and planning characteristics of the building of the educational organization, variability of the organization of the subject content of school premises); psychological safety of the educational environment (indicators: the subjective attitude of younger schoolchildren to the educational environment, satisfaction of younger schoolchildren with significant characteristics of the educational environment, protection of younger schoolchildren from psychological violence in interaction); mobility of technological support for the educational environment (indicators: accessibility of adapted educational resources, adequacy of younger schoolchildren’s ideas about their own educational potential). The key areas of implementation of the event-based approach are: ensuring multilevel management aimed at achieving a synergistic effect from the initiation of educational environment resources based on the principle of subject-oriented reasonable adaptation; the inclusion of primary school students with disabilities in the event community of all participants in educational relations with the prevalence of educational events over traditional events. The research results set the direction for the applied practice-oriented design of a personalized educational space, which will reflect on specific problems and solutions related to the configuration of educational spaces, the creation of tools for designing and evaluating the effectiveness of individual educational trajectories, conditions for the effectiveness of joint and individual forms of pedagogical interaction.